Text Analytic on Halal Research - Ihsanul Ikhwan (SMART Insight, 2021)
The word “halal” experiencing developments in its application in daily life. Traditionally, halal was seen to refer only to meet and poultry, especially refer to the method of slaughter. More recently, this has grown to include non-meet foods such as baked goods, snacks, confectionery, ready-made meals and other processed food and beverage products. as halal is a 'farm-to-fork' process with halal compliance needed all the way through the supply chain, aspects such as warehousing, transportation and logistics all play a role in maintaining and demonstrating halal integrity This study aims to determine the trend development and text analytic on “halal” uses a text analytic method with R tools, which processes the metadata of 884 Scopus indexed articles with the keywords with “halal” in the subject areas of Economics, Econometrics, finance (EEF), and Business, Management, and Accounting (BMA). The results of the text analysis show that the research related to “halal”, dominated by halal food and halal tourism. Further research is needed in other halal industrial sectors, namely halal pharmaceuticals, halal cosmetics, halal media, and halal fashion. This study also indicates that from object side, research documents on halal are still concentred on several countries. Further studies need to be conducted with the case of various countries. Laslty, this paper also provide several recommendations regarding to the theme of future researchs potential about each sectors on halal industry.